Multiple Region of Interest Coverage in Camera Sensor Networks for Tele-Intensive Care Units - Bo Cheng; Lin Cui; Weijia Jia; Wei Zhao; Gerhard, P. Hancke (IEEE transactions on industrial informatics, 2016)
Camera sensor networks (CSNs) are gradually being used in a tele-intensive care unit (tele-ICU), providing useful patient information to remote intensivists. Intensivists wish to focus on different regions of interest (RoIs) containing their patients. We consider a situation where preinstalled camera sensors' locations remain static and they can change the fields of view only by rotating orientations, while the RoIs are dynamically changed in location and size because of changes in the number of patients and care unit configuration. Therefore, an important issue is how to enhance the coverage of these RoIs by controlling the camera sensors' orientations. Previous studies on coverage optimization either focus on single area coverage or point(s) coverage. However, ignoring those multiple RoIs or simply treating them as points can cause unwanted coverage, resulting in performance degradation. In this paper, we investigate a novel multiple RoI coverage (MRC) problem in a CSN-based tele-ICU, aiming to maximize the lowest coverage ratio of all RoIs. The MRC problem is nondeterministic polynomial-time hard, so we propose an efficient heuristic algorithm MRC-Priority to solve it. We have implemented a CSN testbed to evaluate the performance of our proposed algorithm. Experimental results show that our proposed algorithm can improve the lowest coverage ratio up to 200% as compared with existing solutions.